Association of Ascariasis with Nutritional and Anemic Status in Early School-Age Students - Eidwina, Chin Annrie; Faridah, Lia; Ermaya, Yudith Setiati; Akhmad Gurnida, Dida (Althea Medical Journal, 2016)
Background: Ascariasis is one of the most frequent helminthias is that occurred in school-age children. Commonly, severe intensity of infection will seriously affect the nutritional and anemic status of the students. The aim of this study was to determine the association of ascariasis with nutritional and anemic status in early school-age students. Methods: An analytical cross-sectional study was conducted based on the secondary data from Jatinangor Cohort. The secondary data of 74 students who met the criteria were included in this study. Data collection was conducted in the Department of Epidemiology and Biostatistics from August to September 2014. The data obtained was analyzed based on the characteristics of the students regarding gender, age, class, parentsâ education, ascariasis, nutritional and anemic status. Then, the data were further analyzed to determine the association of ascariasis with nutritional and anemic status of the students using the chi square test or Fisher test if the requirement was not fulfilled.Results: Sixteen (22%) students were having Ascaris lumbricoides infection, six (8.1%) students were thin and seventeen (23%) students were anemic. There was no statistically significant association found of Ascaris lumbricoides infection with nutritional and anemic status in early school-age students (P value <0.05) in this study.Conclusions: There is no statistically significant association of Ascaris lumbricoides infection with nutritional and anemic status of the early school-age students. [AMJ.2016;3(1):93â8]Â DOI:Â 10.15850/amj.v3n1.710